1990
DOI: 10.21000/jasmr90010579
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of a Single Application of Municipal Sludge on Abandoned Mine Land

Abstract: Abstract. In 1977, digested and dewatered municipal sludge was applied and incorporated in spoil material at a rate of 184 Mg/ha on a 0.4 ha experimental plot on an abandoned strip mine site in Pennsylvania. Data-were collected for a five-year period (1977)(1978)(1979)(1980)(1981) to determine the effects of the sludge application on the quality and growth of the herbaceous vegetation, the chemical properties of the soil, and the chemical quality of groundwater. In 1989, 12 years after sludge application, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Controlled application to appropriate soil depths in the correct season with consideration of crop harvest and animal grazing undoubtedly minimizes the impact of biosolids application (Smith, 1995); however, these forms of management are unlikely to provide a complete solution to concerns about real or perceived contamination issues. Global standards exist for acceptable biosolids application rates to agricultural land (EPA-VA, 2004;NZWWA, 2003), but much higher amounts may be required to rebuild and rehabilitate forest or mine reclamation land (Sopper and Seaker, 1990). In one study, 20 yr of biosolids application to a plantation forest soil in Washington was shown to have enhanced tree growth without any apparent negative impact on either human health or the environment (Henry et al, 1994).…”
Section: Problems Associated With Land Applicationmentioning
confidence: 99%
“…Controlled application to appropriate soil depths in the correct season with consideration of crop harvest and animal grazing undoubtedly minimizes the impact of biosolids application (Smith, 1995); however, these forms of management are unlikely to provide a complete solution to concerns about real or perceived contamination issues. Global standards exist for acceptable biosolids application rates to agricultural land (EPA-VA, 2004;NZWWA, 2003), but much higher amounts may be required to rebuild and rehabilitate forest or mine reclamation land (Sopper and Seaker, 1990). In one study, 20 yr of biosolids application to a plantation forest soil in Washington was shown to have enhanced tree growth without any apparent negative impact on either human health or the environment (Henry et al, 1994).…”
Section: Problems Associated With Land Applicationmentioning
confidence: 99%
“…2) indicating that this application rate may be insufficient for long‐term neutralization of acidity. Pietz et al (1989a), Sopper and Kerr (1982), and Sopper and Seaker (1990) all reported increases in tailing pH after biosolid application, followed by a decline in pH over several years.…”
Section: Resultsmentioning
confidence: 94%
“…The underlying assumptions were (1) that biosolids would only be applied once at the higher rate and (2) that NO 3 -N leaching losses would be expected, but would not seriously degrade groundwater quality with a one-time application. Detailed research studies in Pennsylvania (Carello, 1990;Sopper and Seaker, 1990) and Virginia (Daniels and Haering, 1994) concluded that application of higher than agronomic rates of various biosolids products to coal mined lands had little, if any, short-or long-term effects on ground water NO 3 -N levels under application areas or at permitted surface water discharge points. Significant NO 3 -N leaching following heavy biosolids applications to forest lands on gravelly coarse-textured soils in the Pacific Northwest has been reported by Riekirk (1978Riekirk ( , 1981, but the observed effects were ephemeral, largely limited to the first two winters after application.…”
Section: Introductionmentioning
confidence: 99%